The neurotoxin of a autochthonous Clostridium botulinum affects the actin cytoskeleton in breast cancer cells - Guarniolo, D (2020)
Botulism is a neuroparalitic disease caused by botulinum neurotoxins (NTBo, serotypes A-G) produced by Clostridium botulinum, whose main reservoir is the soil (Su). Infant botulism is a toxiinfection, caused by ingestion of spores, subsequent colonization and production of toxins in situ. The autochthonous NTBo would correspond to subtype A2, and have higher toxicity than A1 (Botox®), so in the future, they could be used as a therapeutic agent. The NTBos mechanism of action on certain pathologies is still to be clarified. Previous results from our laboratory showed that autochthonous NTBo 1935 from Su, degrades actin of rat brain homogenates, suggesting this protein could be an active target of NTBos. In this work, the action of this NTBo on the actin cytoskeleton in mammary tumor cells was evaluated. The NTBos of Su from strain 1935 and strain A Hall (both serotype A) were purified by saline precipitation. MCF7 cells (breast cancer cells) were cultured in petri dishes or coverslips with 250 LD50 of the NTBos for 25, 45 or 90 min. After incubations, cells were processed for western blot or immunofluorescence in order to evaluate the distribution and expression of actin. NTBo 1935 produced a higher actin degradation and an increased location of this protein at plasma membrane in comparison with A Hall in dependent-time manner. However, at 90 min of treatment, we observed 90% of cytotoxicity and further studies at this time were not evaluated. These results provide new insights about the NTBo mechanism of action and its possible use in the fight against breast cancer.